Metallic and Microbial Contaminants in Drinking Water of Cankiri, Turkey - Emrah Caylak; Mustafa Tokar (E-Journal of Chemistry)
Safe and good quality drinking water is very important for human health. Water provides some heavy metals, such as As, B, Cd, Cn, Cr, Cu, F, Cl, Hg, Ni, Pb, Se, and Sn. These are undesirable substances dangerous to human health and cause chronic diseases and various cancers. Coliform bacteria are a commonly used bacterial indicator of sanitary quality of water. E. coli, total coliform and enterococci have been used as indicators of possible sewage contamination might pose a health risk. In this study, water samples were taken from thirty different waterworks in Cankiri, Turkey and metallic and microbial contaminants were investigated. In the drinking tap water samples have been found at concentrations exceeding the Turkish regulations (As and free Cl) and the WHO guidelines (As and B). Our results also indicate that significant microbiological contaminations were found above the guidelines for drinking waters given by the WHO, because of the fact that in the distribution of water is not appropriate.